PENGARUH TINGKAT KEPERCAYAAN BERKOMUNIKASI DI JEJARING SOSIAL (SOCIAL MEDIA) INSTAGRAM TERHADAP PERILAKU BELI MAHASISWA JURUSAN ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS PANDANARAN SEMARANG - Sinta Petri Lestari (Jurnal Egaliter, 2017)
This study aims to find a significant relationship between the variables of marketing communication in social media Instagram (X) with the purchase decision variable (Y) in Pandanaran University Semarang. This research is descriptive quantitative research with survey method and questionnaire with tools. Respondents of this research is the students of Social Science And Political Science at Pandanaran University Semarang . Sampling technique using the census as many as 78 respondents . Sources of data used primary data and secondary data. The technique of collecting data using questionnaires and literature. Data were analyzed using cross tabulation. The analysis showed that there is a significant relationship, it is characterized a positive correlation coefficient, namely 1) the relationship between the variables of marketing communication (X) with purchase decision variable (Y) is 42%Keywords : marketing communication , mass communication, social media, consumer behavior